TERAPI AIR DINGIN SEBAGAI IKHTIAR PENYEMBUHAN MASALAH KEROHANIAN MENURUT PERSPEKTIF SUNNAH: COLD WATER THERAPY AS AN ATTEMPT TO CURE SPIRITUAL PROBLEMS ACCORDING TO THE SUNNAH PERSPECTIVE - Arip, Najib 'Afif; Mohd Amin, Mohd Zohdi (Maʿālim al-Qurʾān wa al-Sunnah, 2022)
Therapy for the healing of spiritual problems with a cold water is one of the treatment methods practiced by some Islamic Treatment Centers in Malaysia. It is also associated as a method of Islamic medicine, which refers to treatment methods based on the Quran or Sunnah. The main focus of this article is to review the extent of the validity of claims relating to this treatment as one of the methods of Islamic medicine. Research through inductive and descriptive analysis methods on related sources of the Sunnah is carried out. The study seeks to examine and analyze naṣ of syara’ used by Islamic treatment centers as the basis of cold water in the therapy of healing spiritual problems. Several interview sessions were conducted to identify the relationship between the treatment and the sources of the Qur'ān and Sunnah. The results of the interviews found that the processor referred to verse 42 in surah Ṣād regarding the story of the prophet Ayyub as an argument in the use of cold water as the spiritual therapy. They do not refer to any hadith as an argument for this kind of therapy. Meanwhile, searching in Islamic references and hadith collections found as many as 4 hadith that can be used as a basis to support the use of this treatment method as a therapeutic attempt to heal spiritual problems. However, the texts of the hadith do not specifically state about this treatment method, rather they are only general indication for it. While in the implementation aspect, the cold water therapy carried out by the treatment centers involved was found not to contain anything that is against the Islamic Law. Therefore, cold water therapy can be categorized as one of the methods of Islamic medicine.